1970
DOI: 10.1085/jgp.56.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Chromatographic Model of Olfaction

Abstract: The gradient of activity produced along the olfactory mucosa by odorant stimulation was measured by the ratio (the LB/MB ratio) of the summated neural discharges recorded from two branches of the olfactory nerve, a lateral branch (LB) supplying a mucosal region near the internal naris and a medial branch (MB) supplying a region near the external naris. Twenty-four frogs "sniffed" sixteen different odorants, each odorant at four concentrations and two flow rates. Increases in concentration and flow rate produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
1
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 10 publications
11
78
1
1
Order By: Relevance
“…Similar results were obtained with voltage-sensitive dye studies in salamander and frog (Kent and Mozell 1992;Kent et al 1995). These odorant-specific patterns may be attributed to either zonal receptor expression patterns (Buck 1996;Nef et al 1992;Ressler et al 1994;Strotmann et al 1992;Sullivan and Dryer 1996;Vassar et al 1993;, odorant-solubility-related flow patterns (Mozell 1970;Mozell and Jagodowicz 1973;Mozell 1970), or a combination of both (Kimbell et al 1997;Moulton 1976;Cleland 2005, 2006;Yang et al 2007;Zhao et al 2006). …”
Section: Eogs and Odorant Classificationsupporting
confidence: 69%
“…Similar results were obtained with voltage-sensitive dye studies in salamander and frog (Kent and Mozell 1992;Kent et al 1995). These odorant-specific patterns may be attributed to either zonal receptor expression patterns (Buck 1996;Nef et al 1992;Ressler et al 1994;Strotmann et al 1992;Sullivan and Dryer 1996;Vassar et al 1993;, odorant-solubility-related flow patterns (Mozell 1970;Mozell and Jagodowicz 1973;Mozell 1970), or a combination of both (Kimbell et al 1997;Moulton 1976;Cleland 2005, 2006;Yang et al 2007;Zhao et al 2006). …”
Section: Eogs and Odorant Classificationsupporting
confidence: 69%
“…Perireceptor events and/or psychophysical processes are known to be important in olfaction (2,57) and may result in different olfactory percept of isotopomers. For example, it has been proposed that the nasopharyngeal mucus "behaves like a polar chromatographic column" (58), with differential diffusion rates, air/mucus partition coefficients (59), and solubility toward dissolved odorants (60), potentially leading to separation of isotopomers. Because 1 and 1-d 28 are separated by several minutes on a gas chromatographic column (14), and HPLC separation of H/D isotopomers is well known (61), isotopomer fractionation could contribute to perceived differences.…”
Section: Response Of a Human Musk Or To Deuterated And Nondeuteratedmentioning
confidence: 99%
“…Mozell and colleagues (Mozell, 1964(Mozell, , 1970Mozell and Jagodowicz, 1973;Hornung and Mozell, 1977;Mozell et al, 1987;Hahn et al, 1994;Kent et al, 1996;Keyhani et al, 1997) have demonstrated that smaller and more hydrophilic odorants are absorbed rapidly by the aqueous mucosa upon entry into the nasal epithelium, and therefore are likely to have limited access only to the dorsal central channels towards the entrance of the nasal cavity (Schoenfeld and Knott, 2004). On the other hand, larger and more hydrophobic odorants, including octane, were found to be able to disperse more freely throughout the olfactory epithelium than the hydrophilic ones.…”
Section: Glomerular Response Patterns May Emerge From a Combination Omentioning
confidence: 99%